Beyond Co-location: Visual Connections of Staff Workstations and Staff Communication in Primary Care Clinics. Issue 1 (January 2022) - Lim, Lisa; Kanfer, Ruth; Stroebel, Robert J.; Zimring, Craig M.
The importance of communication among healthcare providers has been long recognized, and many healthcare organizations are implementing team-based care, with emphasis on staff communication. While previous empirical studies in various settings illustrate the role of built environments in user communication, there is a lack of quantified interpersonal spatial metrics to predict interactions. This study investigates how interpersonal spatial metrics at different scales predict staff communication patterns by empirically studying four primary care clinics that provide team-based care. We found that staff members in clinics with higher visual connections among staff members reported more timely and frequent communication. We also found that staff members talked to each other more frequently when their workstations were visually connected. The findings of this study are expected to help designers and facility managers provide well-designed team-based clinic layouts, beyond just shared work spaces for team members, for improved staff communication.